A clinical case of successful remission of secondary hemophagocytic lymphohistiocytosis as a result of the use of high doses of normal human immunoglobulin - A. A. Selʹkina; G. E. Lysenko; M. A. Bulygin; E. V. Kryukov; K. V. Kozlov; V. G. Arsentʹev; I. V. Piskarev; A. B. Komissarov; Yu. S. Sergeev; A. M. Shabalov; M. V. Kurtukov (Журнал инфектологии)
The article presents a clinical case of successful application of high doses of normal human immunoglobulin in a patient with secondary hemophagocytic syndrome associated with adenovirus infection, who was in the clinic of infectious diseases of the Military Medical Academy (St. Petersburg). A 17-year-old patient with adenovirus type 55 infection developed multisegmental pneumonia accompanied by acute respiratory failure. Further progression of viral-bacterial pneumonia, prerenal renal damage, development of systemic inflammatory response syndrome was observed. The attending physician suspected secondary hemophagocytic lymphohistiocytosis. A decision was made to perform a sternal puncture. The results of bone marrow aspirate examination revealed characteristic signs of hemophagocytic lymphohistiocytosis: marked activation of macrophage-histiocytic system; 25.6% monocytes with vacuolized cytoplasm; macrophages with phagocytized platelets and normoblasts. The patient was diagnosed as “secondary hemophagocytic lymphohistiocytosis associated with viral infection” on the basis of HLH-2004 criteria (persistent fever, hyperferritinemia, morphologic picture of hemophagocytosis in the bone marrow, cytopenia, splenomegaly) and HScore (244 out of 337 points, 99% probability). Therapy with etoposide 100 mg once and intravenous immunoglobulin at a total dose of 3 g/kg was successful. At the control examination two months later, the patient had no complaints, clinical, laboratory and instrumental methods of examination revealed no abnormalities. No clinical cases of hemophagocytic lymphohistiocytosis associated with adenovirus type 55 have been previously described in the scientific literature.